2018
DOI: 10.3389/fimmu.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani Inhibitor of Serine Peptidases 2 Mediated Inhibition of Lectin Pathway and Upregulation of C5aR Signaling Promote Parasite Survival inside Host

Abstract: Leishmania donovani, the causative agent of Indian visceral leishmaniasis has to face several barriers of the immune system inside the mammalian host for its survival. The complement system is one of the first barriers and consists of a well-balanced network of proteases including S1A family serine proteases (SPs). Inhibitor of serine peptidases (ISPs) is considered as inhibitor of S1A family serine peptidases and is reported to be present in trypanosomes, including Leishmania. In our previous study, we have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…Similarly, all but one publications on Leishmania ecotin orthologs indicated that the main function of these proteins is protection against intestinal proteases in the gut of the insect Ecotin protects bacteria against human serum-mediated lysis vector, or against contact pathway-mediated bactericidal effects of the host [47,48], or downregulation of inflammatory monocytes and monocyte-derived cells [49]. We found only a single, very recent paper reporting that Leishmania donovani ecotin ortholog LnISP2 is not only a neutrophil elastase inhibitor, but also a MASP-2 inhibitor [40]. Notably, however, in that study, recombinant LnISP2 was 50-fold less efficient in providing complete MASP-2 / LP-inhibition, than our recombinant Leishmania major ISP2 ortholog in analogous tests.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, all but one publications on Leishmania ecotin orthologs indicated that the main function of these proteins is protection against intestinal proteases in the gut of the insect Ecotin protects bacteria against human serum-mediated lysis vector, or against contact pathway-mediated bactericidal effects of the host [47,48], or downregulation of inflammatory monocytes and monocyte-derived cells [49]. We found only a single, very recent paper reporting that Leishmania donovani ecotin ortholog LnISP2 is not only a neutrophil elastase inhibitor, but also a MASP-2 inhibitor [40]. Notably, however, in that study, recombinant LnISP2 was 50-fold less efficient in providing complete MASP-2 / LP-inhibition, than our recombinant Leishmania major ISP2 ortholog in analogous tests.…”
Section: Discussionmentioning
confidence: 93%
“…Ecotin has been identified as virulence factor for several pathogenic Gram negative bacteria such as Yersinia and Burkholderia species and two species of the eukaryotic unicellular pathogen, Leishmania as well [8][9][10]40].…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining revealed LdISP close to the flagellar pocket of L. donovani strain AG83 promastigotes, which is compatible with putative secretion of ISP for the inhibition of the NE at the surface of macrophages (25). In another study, recombinant LdISP2 was reported to inhibit the complement-related serine peptidase mannan-binding lectin serine protease (MASP)-2, whereas it did not inhibit MASP-1 or the C1 complex (26). However, inhibitory activity was only observed at nonphysiologic concentrations of recombinant LdISP2 (>5 μM), and inhibition of C4b formation was only achieved at >10 μM of LdISP2, suggesting that those peptidases are unlikely to be a target of ISP2 in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies applying treatment of infected RAW cells with recombinant LdISP2 showed slight reduction of infection and of NO production (25). Recombinant LdISP2 was recently shown to inhibit the complement-related serine peptidases and C3c and C5c generation (26). However, the ISP 2 gene is truncated in the genome of the L. donovani reference strain BPK282A1, suggesting that some L. donovani strains might not express a functional ISP2 inhibitor, which could influence the control of serine peptidase activity during infection.…”
mentioning
confidence: 99%
“…Parasites express various proteins to effectively play these roles ( Morais et al, 2018 ; Song et al, 2018 ). Increasing evidence reveals that parasites escape complement attack by using several approaches, including expression of proteins to capture host regulatory proteins; expression of proteins that are homologous to host regulators and interfere with the functions of the host complement system ( Jozsi, 2017 ); and expression of proteins that specifically bind to host complement components and interfere with the final formation of the MAC by inhibiting the classical, lectin, or alternative activation pathways ( Braschi and Wilson, 2006 ; Zhao et al, 2017 ; Mendes-Sousa et al, 2018 ; Verma et al, 2018 ). In this review, we compiled pertinent information regarding parasitic abilities to escape host complement attack as a survival strategy in the hostile environment, and the mechanisms underlying complement evasion.…”
Section: Introductionmentioning
confidence: 99%